Racisms In Digital Media Space - Titley, Gavan; Nikunen, Kaarina; Pantti, Mervi; Sharma, Sanjay; Siapera, Eugenia; Viejo Otero, Paloma; Morero, Elena; Matamoros Fernandez, Ariadna; Highfield, Tim; Muench, Felix (AoIR Selected Papers of Internet Research, 2017)
Racism in digital media space is motile and dynamic; it is propagated online and circulated across social media platforms, it is transnationally assembled from an expansive repertoire of digital artefacts, it is concentrated and generated by spectacles and viral events. In the context of the ’borders crisis’ since 2014, where ’fake news’ items about refugees have been laundered from a plethora of sites into mainstream news circulation, it is also clear that ’internet racism’ has assumed important forms of socio-political productivity. Public discussions of the vitality of digital racism have proliferated, yet perhaps unsurprisingly they have tended to reproduce established images of the ’online extremes’, focusing in on the problem of anonymity; or the extent of hate speech; or the ambivalence of technology, or the responsibilities of individuals and platforms. Concomitantly, the generativity of this multi-modal racism has been under-researched in academic contributions, where, an influential literature on race and the internet notwithstanding, much of the prominent research has tended to focus on the Internet and political extremism, and the question of ’hate speech’ online. The aim of this panel is to propose approaches to racism online that are adequate to key formative dimensions: its significance in the socio-political conjuncture; the techno-social material relations of production and distribution; and the (social) media dynamics of circulation and assemblage. Each paper foregrounds a different theoretical and methodological dimension of the discussion based on contextually variant case studies and data samples. The first paper, examining the recent dynamics of the ’immigration debate’ in Finland, proposes the necessity of examining how racism is affectively produced within intensive media spectacles. This paper situates its discussion in relation to Chadwick’s (2013) concept of the ’hybrid media system’ - a way of examining the contingency of power relations as spectacles take shape in and across ’mainstream’ and ’social’ media platforms. Through these dynamics, the paper argues, the reflexive question as to what constitutes racism, and who is empowered to decide, is frequently a recursive dimension of cross-media events. The second paper moves beyond this focus on spectacular events to add further categories for thinking about the ’multi-modal’ production of online racism. Conceiving of online racism as an assemblage, it argues that we can only understand racism online if we conceive of the deep entanglement of racism and the web, and of the ways in which a racialized ’affective economy’ is constituted by spectacular, explicit and ambient racisms. The third paper uses a specific spectacular event to investigate the role of visual objects as ’key mediators’ and drivers of debates and conflicts over race and racism online. Drawing on network visualisations and Twitter data, it analyses the specifically national modality of a transnational viral event, examining reactions to an image to tease out the varying and often antagonistic ways in which what constitutes racism is argued for in public culture. The final paper confronts the current and often over-determining focus on ’hate speech’ by examining the field of tensions and influences within which legislative and policy responses are formed and articulated. It contrasts the understandings and operative terms of institutional and legal responses that inform policy; the public relations and policy shifts of social media platforms in relation to reporting and removal mechanisms; and the goals and tactics of anti-racist groups who have turned to social media hate speech as a field of activism. It argues that the former two agencies work to foreclose any political understanding of hate speech in relation to the wider conjunctural and techno-social questions of racism this panel seeks to explore.